Digital transformation to the sustainability of public relations profession in the era of disruption - Pribadi, Arguanda; Nasution, Nurhasanah (Universitas Ahmad Dahlan, 2021)
Digital transformation is a change in the way work is handled by using information technology to gain efficiency and effectiveness. Since April 2011 the government has echoed Indonesia 4.0, through the ministry of the industry it has made Indonesia 4.0 a Roadmap that has been integrated as the implementation of many strategies in entering the industrial era 4.0. The public relations profession has become a target for the era of technological disruption 4.0 which is capable of producing big data, analytic data, artificial intelligence, internet of things (IoT) which exponentially boosts the quality and effectiveness of various public relations functions. This research is a qualitative descriptive study that aims to conduct in-depth interviews with predetermined respondents. This type of research uses field research, namely research that goes to the field to make observations about a phenomenon in a scientific situation. The data were obtained from two sources including one Pertamina MOR I Medan worker and one Head of BPC Perhumas Medan. The data analysis technique used is data reduction which is the process of selecting, focusing on simplification, and transforming data that arise from written records and research locations. Based on the research results obtained through interviews with resource persons, human performance opportunities in the public relations profession still have a good and exciting future for the world to be disrupted because this era will become rivals for public relations practitioners to be more advanced. Because artificial intelligence (AI) can support and facilitate public relations practitioners in carrying out their duties.